1986
DOI: 10.1093/cvr/20.9.658
|View full text |Cite
|
Sign up to set email alerts
|

Changes in creatine phosphate, inorganic phosphate, and the purine pattern in dog hearts with time of coronary artery occlusion and effect thereon of mioflazine, a nucleoside transport inhibitor

Abstract: A detailed analysis was made of the changes in canine myocardium, with time of occlusion, in several important metabolites such as creatine phosphate and adenosine triphosphate (luminometry), inorganic phosphate (spectrophotometry), and most of the purines and nicotinamide adenine dinucleotide (high performance liquid chromatography). Within 1 min there was a significant reduction in creatine phosphate and a significant increase in inorganic phosphate, adenosine diphosphate, and adenosine monophosphate. A decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…Eight were pretreated 150 min before LAD occlusion with 2.5 mg. kg 1 orally of mioflazine (R 51 469 -Janssen Pharmaceutica, Beerse, Belgium) and the others served as controls. Further preparation and LAD occlusion was done as described previously (3,15). Control transmural needle biopsies were taken from the non-occluded area, one before ischemia and one at the end of the experiment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight were pretreated 150 min before LAD occlusion with 2.5 mg. kg 1 orally of mioflazine (R 51 469 -Janssen Pharmaceutica, Beerse, Belgium) and the others served as controls. Further preparation and LAD occlusion was done as described previously (3,15). Control transmural needle biopsies were taken from the non-occluded area, one before ischemia and one at the end of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…In most animals this procedure was repeated a second time and from several dogs a sample could be obtained after a third 8-min occlusion. The biopsies were processed and analysed for the different metabolites, exactly as described earlier (15). The final results are expressed as Ixmoles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NBMPR, on the other hand, is unlikely to be tested in humans despite its effectiveness as a transport inhibitor and host protector since it is a nonproprietary drug. Recently we explored a number of derivatives of mioflazine, a new cardioprotective drug, 24 and it appears that some of these will be useful for host protection in selected species, with potential for oral administration and long duration of action.…”
Section: Selection Of Nucleoside Transport Inhibitorsmentioning
confidence: 99%
“…Myocardial ischaemia is associated with the intracelshown to exert deleterious effects on isolated mitolular accumulation of various factors known to be chondria including inhibition of oxidative phosassociated with tissue injury, including long-chain phorylation and adenine nucleotide (ADP/ATP) acyl CoA (Opie, 1979;Piper & Das, 1987), inorganic translocase activity (Opie, 1979;Shug, 1979;Ferrari phosphate (Pi) (van Belle et al, 1986) and free radet al., 1988). Various investigators have shown that icals (Garlick et al, 1987).…”
Section: Introductionmentioning
confidence: 99%